Maintenance of sterility in SMS packaging in dental environments: concern with biosafety - Júlia Pereira Carvalho Almeida; Robert Willer Farinazzo Vitral; Aneliese Holetz de Toledo Lourenço; Georgia Botafogo Pinheiro das Flores e Cruz D'almas Coxiponés; Ana Bárbara Polo; Ana Carolina Morais Apolonio (Universidade Estadual de Maringá, 2022)
Healthcare services must be guided by biosafety practices and microbial control. This control is highly influenced by humidity, which directly impacts the maintenance of sterility of the materials used in the appointments. High concentration of moisture, in the form of aerosol, splashes and spills, is caused during dental care. During the COVID-19 times the contamination by aerosol and droplets worries greatly. Considering that it could cause harm to the sterility of an autoclaved material, especially in dental environments, the objective was to evaluate the behavior of SMS sterilization packages (Spunbonded / Meltblown / Spunbonded) against microbial penetration in an aqueous vehicle. SMS of three brands were challenged, equally divided into two groups: virgin and processed (subjected to a single autoclaving cycle). Each specimen was aseptically deposited on Macconkey agar. Subsequently, 5 µL of Escherichia coli ATCC 25922 saline solution [108 CFU mL-1] was deposited in center of the SMS specimen and the dish incubated at 36°C / 48h. Reading was performed by the presence or absence of bacterial growth typical of the species under the SMS, observed on the back of Petri dish. The lowest penetration rate observed was 60% for one of the brands in the virgin condition, and 75% for two brands in the processed condition. Statistical analysis showed an association between bacterial penetration and the evaluated group, this association being valid only in the virgin condition. The different SMS behave similarly in terms of resistance to bacterial penetration after being processed. The data show that moisture can assist in bacterial transport through sterilized SMS. Therefore, SMS packages are not able to prevent bacterial penetration, and possibly other microorganisms, when in aqueous vehicles, offering a potential risk of breaking the aseptic chain. Thus, care must be taken in routines for handling and storage sterile packaging.